May Day manifesto, 1941 (1941)
1941 1939-1945 "May Day manifesto, 1941" [HFR0225], 1941 Issued by the National Council of Labour [the TUC and Labour Party], the manifesto focuses on an appeal to German workers to overthrow the Nazi Dictatorship.